An Ecosystemic Approach to Male Grief Response to Perinatal Loss - Fátima Esther De Lima Pinasco; María Carolina Farías Rodríguez (Universitat de Barcelona, 2024)
Perinatal death is framed within a social context where it is not explicitly recognized as «the death of a baby». Perinatal loss is a very frequent reality and has a high impact on the family. However, it is a grief that is experienced in great solitude. Ecosystem theory with its ecological perspective understands that human development is influenced by relationships with its environment. Perinatal Psychology seen from an ecosystem approach allows a broad and flexible view. In this sense, there is a lack of empathy regarding the pain that the male father is going through regarding the death of his/her child, which can lead to helplessness and a feeling of marginalization in the face of their experience. Within a patriarchal culture, the concept of paternity is associated with a man's ability to get pregnant and his ability to be an economic provider. The identity of men is still linked to the construction of masculinity, which is in contrast to reproduction. Faced with loss, the man plays the role of supporting the woman, generating limitations in being able to express her own discomfort. These learn to identify with reason and make an abrupt cut from the bodily and emotional experience. This way of experiencing grief does not allow them to navigate the loss, avoiding connecting with their own sensitivity, which feeds back into the paradigm.